2007
DOI: 10.1080/13651820701713758
|View full text |Cite
|
Sign up to set email alerts
|

Single hepatocellular carcinoma ranging from 3 to 5cm: radiofrequency ablation or resection?

Abstract: Even if RES seemed to promise better long-term results, in the medium term this difference had no statistical significance. Survival in this series was more closely related to the stage of the underlying liver disease than to treatment (RES/RFA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…5). Similar findings were also noted in other reports [12,13,14,15,16,17,18]. Based on these, resection is recommended for cases with 3 or fewer tumors 3 cm or smaller in which resection is readily applicable with regard to the liver function and localization, and only a small amount of liver tissue is sacrificed, but RFA is recommended for tumors located in a deep region, when the liver function capacity is graded as Child-Pugh B, or the tumor extends over the bilateral lobes.…”
Section: Outcomes and Survival Following Rfa: Comparison With Those Asupporting
confidence: 81%
“…5). Similar findings were also noted in other reports [12,13,14,15,16,17,18]. Based on these, resection is recommended for cases with 3 or fewer tumors 3 cm or smaller in which resection is readily applicable with regard to the liver function and localization, and only a small amount of liver tissue is sacrificed, but RFA is recommended for tumors located in a deep region, when the liver function capacity is graded as Child-Pugh B, or the tumor extends over the bilateral lobes.…”
Section: Outcomes and Survival Following Rfa: Comparison With Those Asupporting
confidence: 81%
“…3-6,8,18 -20 Thus, in previous series, complete ablation rates for larger HCCs (3-5 cm) after RFA seem unfavorable, ranging from 61.3% to 82.5%. 21,22 Although these results are presumably outdated thanks to recent technical progress, 23 some authors suggested that RFA could be considered as an effective first-line treatment only for very small HCC (Յ2 cm). 12 Thus, to improve local tumor control for larger nodules, the combination of RFA with TACE is increasingly advocated.…”
mentioning
confidence: 99%
“…Studies comparing the efficacy of surgery and local ablative therapies in small and medium-sized HCCs have clearly demonstrated that a wellperformed local ablation yields similar survival rates and less morbidity compared to surgery (14)(15)(16). Therefore, it is generally recognized that RFA can be used as the first-line treatment for HCC ≤5 cm.…”
Section: Discussionmentioning
confidence: 99%